Histopathological Profile of Lung Cancer: A Single-Center Study from Nepal - Paudel, Bishal; Dhungana, Reechashree; Shrestha, Rakshya; Panthi, Bishal; Kharel, Sanjeev (Journal of Institute of Medicine Nepal, 2025)
Introduction Lung cancer remains the leading cause of cancer-related mortality globally, accounting for approximately 18% of all cancer death. Despite the global prevalence of lung cancer, epidemiological data from Nepal remain limited. The study aims to bridge these gaps by investigating the histopathological characteristics of lung cancer in a cohort of patients from a tertiary care center in Nepal. Methods This is an observational cross-sectional study conducted at Tribhuvan University Teaching Hospital (TUTH) among lung cancer patients aged greater than 18 years of age from September 2024 to February, 2025. Descriptive statistics was used to summarize demographic and histopathological characteristics. Results A total of 107 lung cancer patients were included in our study. The male:female ratio was 1.3 in our study, while the mean age of the patients was 67 years and standard deviation is 11 years. Squamous cell carcinoma (48%) and Adenocarcinoma (46%) were the major histological subtypes while only 6% cases were Small-cell carcinomas. Conclusion This study analyzes the histopathological and the demographic profile of lung cancer diagnosed at a single tertiary center of Nepal. Non-small cell lung cancer is the most common histological diagnosis in this study. Broader study is needed to explore the clinical and molecular associations.